Untargeted Metabolomics Reveals Multiple Phytometabolites in the Agricultural Waste Materials and Medicinal Materials of Codonopsis pilosula - Zeng, Xu; Li, Jiaxue; Lyu, Xinkai; Chen, Juan; Chen, Xiaomei; Guo, Shunxing (Frontiers in Plant Science, 2022)
Codonopsis pilosula has been used in traditional Chinese medicine for hundreds of years, where it has been used to treat anaemia, fatigue, a weak spleen, and stomach problems, among other ailments. The roots of C. pilosula are considered medicinal, while the aerial parts are always directly discarded after harvest in autumn or winter. Some studies have shown that the stems and leaves of C. pilosula also contain a variety of active metabolites, including saponins, flavonoids, terpenoids, and polysaccharides. To efficiently utilise resources, waste products from C. pilosula leaves and stems were analysed by untargeted metabolomics and chemometrics. A total of 1508 metabolites were detected and annotated, of which 463 were identified as differentially expressed metabolites (DEMs). These DEMs were grouped into classes, such as carboxylic acids and derivatives, steroids, organic oxygen compounds, fatty acyls, prenol lipids, and flavonoids. Metabolic profiling of C. pilosula tissues showed that the contents of polyacetylenes, polyenes, flavonoids, some alkaloids, steroids, terpenoids, and organic acids were higher in stems and leaves, whereas the contents of the main lignans and some alkaloids were more enriched in roots. Moreover, C. pilosula stems and leaves also contained a lobetyolin, syringin and atraetylenolide III, which were detected by LC-MS/MS and HPLC-UV. The extracts of C. pilosula aerial parts also showed stronger antioxidant properties than roots. C. pilosula stems and leaves were rich in active ingredients and might have great value for development and utilisation.